MEKANISME PERDAGANGAN EFEK SYARIAH DI BURSA EFEK INDONESIA PERPEKTIF FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA - Alfiah, Esti (Institut Agama Islam Bengkulu, 2017)
Abstract : Mechanisms of shariah trading securities at Stock Exchange Indonesia based on the Fatwa National Shariah Board (DSN-MUI) can be basis for investors to invest in shariah securities. As a whole, trading mechanism at Stock Exchange Indonesia based on the Fatwa National Shariah Board (DSN-MUI) has been appropriately implemented. This subject is seen from the criteria indicator to issue Shariah-compliant securities, securities trading mechanisms, types and prohibited transactions, and sharia securities. However, there are still a guilt like a lack of information that is given by brokers so that customers get the wrong information such as fees and contracts made more likely to be destined for brokers (companies).Keywords: Sharia Trading Securities, Shariah Mutual Fund and Shariah Stock, Fatwa DSN-MUI